Frequent BRAF mutation in early-onset colorectal cancer in Taiwan: association with distinct clinicopathological and molecular features and poor clinical outcome. Issue 4 (23rd October 2015) - Tsai, Jia-Huei; Liau, Jau-Yu; Lin, Yu-Lin; Tseng, Li-Hui; Lin, Liang-In; Yeh, Kun-Huei; Jeng, Yung-Ming
Abstract : Background: Occurrence of early-onset colorectal cancer (EOCRC) under the age of 30 is very rare and the molecular characteristics are poorly understood. A low BRAF mutation rate has been noted in several studies of EOCRC from Western countries. Aims: To determine the clinicopathological and molecular features of EOCRCs in Taiwan. Methods: KRAS / BRAF gene mutation, mismatch repair protein immunohistochemistry, microsatellite instability and CpG island methylation phenotype analyses were examined to determine the molecular characteristics of EOCRC. Results: Sixty-six patients with EOCRC at our hospital between 2000 and 2012 were studied. BRAF mutation was detected in 11 of the 59 tumours analysed (19%) and the rate was significantly higher than the overall BRAF mutation rate of colorectal cancer in patients older than 30 years (p<0.001). Clinically, 9 of 11 patients with BRAF- mutated tumours presented with advanced-stage diseases and they presented significantly more frequently with stage IV disease than those with BRAF wild-type tumours (p=0.042). Histologically, BRAF mutation was associated with a poorly differentiated histology, a serrated precursor polyp and focal signet ring cell differentiation (p=0.042, 0.008 and 0.008, respectively). None of the BRAF -mutated tumours was mismatch repair protein-deficient and/or microsatellite instability-high. Overall survival of patients with BRAF -mutated tumours was significantly worse than that of patients with BRAF wild-type tumours, despite adjustment for the disease stages and tumour differentiation. Conclusions: BRAF mutation was frequent in EOCRCs in Taiwan and was associated with distinct clinicopathological and molecular features.